THU0570 EXPERTS' VIEWS ON THE IMPACT OF REHABILITATION FOR PATIENTS WITH RHEUMATOID ARTHRITIS IN AUSTRIA. (2nd June 2020) - Oppenauer, C.; Böttcher, E.; Eberl, G.; Falkenbach, A.; Habelsberger, W.; Kirchheimer, J.; Kullich, W.; Mur, E.; Oliveira-Sittenthaler, C.; Stummvoll, G.; Wiederer, C.; Zeindler, H.; et al.
Abstract : Background: Rehabilitation methods and standards for patients with rheumatoid arthritis (RA) have significantly changed due to more efficient medication improving the course of the disease. Therefore, physical activity, participation, disease management and patient education are most important goals in rehabilitation of patients with RA. Objectives: Aim of this study was to evaluate the significance and impact of rehabilitation methods according to the subjective attitudes and views of experts and professionals in the field of RA. Opinions of members of the task force (TF) "Rehabilitation" of the Austrian Society of Rheumatology (ÖGR) were compared to the estimation of the other members of the ÖGR. Methods: All members of the ÖGR were invited to participate in an online survey to rate the impact of rehabilitation for patients with RA between 0 (no impact) and 10 (high impact). Besides sociodemographic and experience related data about the experts and professionals, two main issues were investigated: (1) Impact of rehabilitation related to specific interventions (2) Impact of rehabilitation methods for patients with RA according to different disease and treatment points. Results: 129 members (50% male, 50% female) of the ÖGR participated in the online survey. 12 persons were members of the TF "Rehabilitation" of the ÖGR. 11 (8.6%) respondents were general physicians, 66 (51.6%) specialists in internal medicine with further expertise in rheumatology, 15 (11.5%) specialists in internal medicine, 14 (10.9%) specialists for physical medicine with further expertise in rheumatology, 2 (1.6%) specialists in orthopaedics, 13 (10.2%) health professionals and 7 (5.5%) persons were from other profession categories such as researchers for example. The majority of respondents (80%) worked already more than five years with patients with RA in a stationary setting. Results of the online survey demonstrate that the ranking of the impact of specific rehabilitation interventions did only marginally differ between the two person groups: Both groups ranked the importance of occupational and physical therapy the highest. Only the subjective importance of splints and assistive technologies was higher assessed by the general members of the ÖGR. Further, the ranking about the estimated impact of rehabilitation methods for patients with RA was very similar between the two person groups: The importance of rehabilitation for patients with functionality restrictions and for patients with RA in the first years of their disease was ranked the highest by both groups. Conclusion: Results of the online survey demonstrate that ratings related to the impact of rehabilitation interventions for RA patients do only slightly differ between the investigated member groups of the ÖGR. Finally, the results indicate that rehabilitation methods for RA patients and rehabilitation related knowledge are well accepted and successfully transferred into disease management of patients with RA by professionals and experts in rheumatology in Austria. Disclosure of Interests: Claudia Oppenauer: None declared, Elke Böttcher Grant/research support from: UCB, Roche, MSD, Speakers bureau: UCB, Pfizer, BMS, MSD, Roche, Amgen, Lilly, Gabriele Eberl: None declared, Albrecht Falkenbach: None declared, Winfried Habelsberger: None declared, Johannes Kirchheimer: None declared, Werner Kullich Shareholder of: Roche Stocks, Grant/research support from: MedTec Company, Germany - MedizinTechnik, Erich Mur: None declared, Christa Oliveira-Sittenthaler: None declared, Georg Stummvoll Speakers bureau: Lilly, Roche, gsk, Christian Wiederer Consultant of: Firma Grünenthal, Thema Capsaicin, Dezember 2019, Harald Zeindler: None declared, Valerie Nell-Duxneuner Speakers bureau: MSD, Pfizer, Jansen, Abbvie, Lilly, Novartis